If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + yi)(3 + 2i) + -1z = (9 + -2i) Reorder the terms: (iy + x)(3 + 2i) + -1z = (9 + -2i) Multiply (iy + x) * (3 + 2i) (iy(3 + 2i) + x(3 + 2i)) + -1z = (9 + -2i) ((3 * iy + 2i * iy) + x(3 + 2i)) + -1z = (9 + -2i) ((3iy + 2i2y) + x(3 + 2i)) + -1z = (9 + -2i) (3iy + 2i2y + (3 * x + 2i * x)) + -1z = (9 + -2i) Reorder the terms: (3iy + 2i2y + (2ix + 3x)) + -1z = (9 + -2i) (3iy + 2i2y + (2ix + 3x)) + -1z = (9 + -2i) Reorder the terms: (2ix + 3iy + 2i2y + 3x) + -1z = (9 + -2i) (2ix + 3iy + 2i2y + 3x) + -1z = (9 + -2i) Remove parenthesis around (9 + -2i) 2ix + 3iy + 2i2y + 3x + -1z = 9 + -2i Solving 2ix + 3iy + 2i2y + 3x + -1z = 9 + -2i Solving for variable 'i'. Reorder the terms: -9 + 2i + 2ix + 3iy + 2i2y + 3x + -1z = 9 + -2i + -9 + 2i Reorder the terms: -9 + 2i + 2ix + 3iy + 2i2y + 3x + -1z = 9 + -9 + -2i + 2i Combine like terms: 9 + -9 = 0 -9 + 2i + 2ix + 3iy + 2i2y + 3x + -1z = 0 + -2i + 2i -9 + 2i + 2ix + 3iy + 2i2y + 3x + -1z = -2i + 2i Combine like terms: -2i + 2i = 0 -9 + 2i + 2ix + 3iy + 2i2y + 3x + -1z = 0 The solution to this equation could not be determined.
| 13/3-7x=5 | | 4k+2=5.6 | | .2x+x=81 | | 3x+4z=6+5y | | 5x=6+2 | | (3-2i)-z(1+i)+i=zi | | -3(-3w^2-1+x^3)= | | (2x+3)(7x-2)= | | 8x-22=3(3x+11)-6x | | 180/11 | | 2c/f-k=r | | 3x=5/2 | | 12m-11=9m+1 | | x=4(p-12) | | (x-3)(2x^2-2)=0 | | 7-2(x-4)=21-5x | | 9-2(3x-4)= | | 8-3(2x+5)=-4x-(x+4) | | x+x=185 | | 1.25*((0.3141*x)+x)=7586.81 | | -8x+4(1+5n)=-6-14 | | (4x+2)(3x-3)= | | x/-45/6 | | 8=(5)(12) | | 5x+10-2x=x-4 | | 0.25*((0.3141*x)+x)=7586.81 | | z(3-2i)+(5-5i)=(1-i)+z | | F(-3)=3x+12 | | 1.75x+2.25y=20.50 | | m-5=35 | | 7x+52=5x+44 | | (0.3141*x)+x=7586.81 |